What B cell memories are made of. (April 2019) - Tomayko, Mary M; Allman, David
Highlights: Different memory B cells can take on different functions. Many memory B cells appear to be exceptionally long-lived. IgM-positive memory B cells may play unique and poorly understood roles in host protection. T-cell independent antigens also often induce lasting antibody titers. Abstract : In many ways, memory B cells represent the ultimate outcome of humoral immunity. Many of these cells express exceptionally high affinity antigen-specific B cell receptors for antigen, and these cells are a critical source of the long-lived plasma cells that secrete protective serum antibodies to protect against secondary exposure to pathogens and other life-threatening antigens. Evidence is now emerging that not all memory B cells are created via the same cellular pathways and molecular events. Similarly, it is becoming clear that different memory B cells can take on different functions, with some producing IgM rather than IgG antibodies upon reactivation, and others preferentially producing plasma cells rather than additional waves of memory B cells. With this review, we discuss the conceptual ides and early studies surrounding early work on B cell memory, then discuss the many pathways and functional attributes of subpopulations of memory B cells and current approaches to characterize these cells directly.